cứu với >< Câu 2. Tìm x biết : c) 2 ^ 3 + 4(x – 2) = (- 4) ^ 2 / 2 d) (2x – 4)(5 + x) = 0 b) 3x – 7 = – 58 a) 12 + 2x = 6

cứu với ><
Câu 2. Tìm x biết :
c) 2 ^ 3 + 4(x – 2) = (- 4) ^ 2 / 2
d) (2x – 4)(5 + x) = 0
b) 3x – 7 = – 58
a) 12 + 2x = 6

2 bình luận về “cứu với >< Câu 2. Tìm x biết : c) 2 ^ 3 + 4(x – 2) = (- 4) ^ 2 / 2 d) (2x – 4)(5 + x) = 0 b) 3x – 7 = – 58 a) 12 + 2x = 6”

  1. Answer:
    \bb c)
    2^3+4.(x-2)=(-4)^2/2
    8+4x-8=16/2
    4x=8
    x=2
    Vậy x=2
    $\\$
    \bb d)
    (2x-4).(5+x)=0
    **TH1:
    2x-4=0
    2x=4
    x=2
    **TH2:
    5+x=0
    x=-5
    Vậy x=2 hoặc x=-5
    $\\$
    \bb b)
    3x-7=-58
    3x=-58+7
    3x=-51
    x=(-51):3
    x=-17
    Vậy x=-17
    $\\$
    \bb a)
    12+2x=6
    2x=6-12
    2x=-6
    x=(-6):2
    x=-3
    Vậy x=-3

    Trả lời
  2. c, 2^3 + 4(x-2) = {(-4)^2}/2
    => 8 + 4x – 8 = 16/2
    => 4x = 8
    => x = 2
    Vậy x = 2

    d, (2x-4)(5+x) = 0
    TH1: 2x – 4 = 0
    => 2x = 4
    =>x =2
    TH2: 5 + x = 0
    =>x = -5
    Vậy x = 2; x= -5

    b, 3x – 7 = -58
    => 3x = -58 + 7
    => 3x = -51
    => x = (-51) : 3
    => x = -17
    Vậy x = -17

    a, 12 + 2x = 6
    => 2x = 6 – 12
    => 2x = -6
    => x = -3
    Vậy x = -3

     

    Trả lời

Viết một bình luận

Câu hỏi mới